Adverse Events Associated With Therapeutic Endoscopic Retrograde Pancreatography. Issue 3 (March 2021) - Han, Samuel; Attwell, Augustin R.; Tatman, Philip; Edmundowicz, Steven A.; Hammad, Hazem T.; Wagh, Mihir S.; Wani, Sachin; Shah, Raj J.
Abstract : Objectives: Data regarding the safety of endoscopic retrograde pancreatography (ERP) are limited compared with biliary endoscopic retrograde cholangiopancreatography. The aim of this study was to determine adverse events (AEs) associated with therapeutic ERP. Methods: This single-center retrospective study examined consecutive therapeutic ERPs with the primary intention of cannulating the pancreatic duct. Multivariate logistic regression was performed to identify risk factors for AEs. Results: A total of 3023 ERPs were performed in 1288 patients (mean age, 50.3 years; 57.8% female) from January 2000 to January 2017. Overall AE rate was 18.9% with abdominal pain requiring admission (9.8%) and post-ERP pancreatitis (5.7%) being most common. On multivariate analysis, female sex (adjusted odds ratio [aOR], 2.3; 95% confidence interval [CI], 1.9–2.9), acute recurrent pancreatitis (aOR, 5.0; 95% CI, 1.7–15.3), chronic pancreatitis (aOR, 1.8; 95% CI, 1.3–2.6), and pancreatic sphincter of Oddi dysfunction (aOR, 2.1; 95% CI, 1.4–3.3) were associated with an increased risk of overall AEs. Pancreatic sphincterotomy (aOR, 1.9; 95% CI, 1.5–2.4) and therapeutic stenting (aOR, 1.6; 95% CI, 1.2–2.2) also increased the risk of AEs. Conclusions: Nearly 1 in 5 patients who undergo therapeutic ERP will experience an AE; however, the rates of major AEs, including post-ERP pancreatitis, bleeding, and perforation, are low. Abstract : Supplemental digital content is available in the text.